Characterization of Non-Associative Ordered Semigroups by the Properties of F-Ideals. Issue 4 (1st October 2020) - Kausar, Nasreen; Munir, M.; Kousar, Sajida; Gulistan, M.; Anitha, K.
Abstract : In this article, we present brief description on R-OAG-gpd ( regular ordered AG-groupoid ) and IR-OAG-gpd ( intra-regular ordered AG-groupoid ) by using FL-ideal, FR-ideal, FQ-ideal, FB-ideal, FB-ideal, FGB-ideal.